Web-Based Community Data Collection for the Family Hope Program in Jakabaring Sub District - Maharani, Mutiara; M, Dona (Journal of Computer Science Application and Engineering (JOSAPEN), 2023)
This paper addresses the need for an information system to manage data for the Family Hope Program (PKH) in Jakabaring Sub District, Palembang City, Indonesia. The PKH aims to provide assistance to Very Poor Households (RTSM), intending to alleviate immediate burdens and break the cycle of poverty across generations. The absence of a dedicated information system has led to frequent data loss, prompting the proposal and development of a structured system to enhance data collection, processing, and management. Employing the Waterfall model, the system development approach was meticulously structured, progressing through sequential stages—analysis, design, coding, testing, and implementation. The system's design components, including Use case diagrams, Activity diagrams, Sequence diagrams, and Class diagrams, were crucial in outlining functionalities and relationships within the proposed system. Notably, the proposed system's interface, exemplified by an admin dashboard, offers a user-friendly layout featuring population graphs and intuitive menus for data management and reporting. Black Box testing results exhibited satisfactory performance across various system functionalities, affirming its potential to efficiently manage data for the PKH. Overall, this proposed information system stands as a promising solution to mitigate data loss challenges and enhance efficiency in supporting Very Poor Households in Jakabaring Sub District.